Metformin Effects on FOXP3+ and CD8+ T Cell Infiltrates of Head and Neck Squamous Cell Carcinoma. (8th October 2019) - Amin, Dev; Richa, Tony; Mollaee, Mehri; Zhan, Tingting; Tassone, Patrick; Johnson, Jennifer; Luginbuhl, Adam; Cognetti, David; Martinez‐Outschoorn, Ubaldo; Stapp, Robert; Solomides, Charalambos; Rodeck, Ulrich; et al.
Abstract : Objectives: Alterations of cellular metabolism have been implicated in immune dysfunction in the tumor microenvironment (TME) of head and neck squamous cell carcinoma (HNSCC). Metformin has recently emerged as a candidate of interest for combination with immunotherapy in HNSCC. This study investigated the effect of metformin on immune cell infiltrates of HNSCC. Methods: Retrospective analysis of T cell infiltrates in primary tumor specimens from patients enrolled in a clinical window of opportunity trial of presurgical metformin. Metformin was titrated to a standard diabetic dose (2000 mg/day) for a minimum of 9 days (mean 13.6 days) prior to surgical resection. Pre and posttreatment surgical specimens from 36 patients (16 HPV +, 20 HPV − ) were comparatively analyzed. FOXP3 + and CD8 + immune cell infiltrates in the tumor and peritumoral stroma of pre and posttreatment HNSCC specimens were quantified by digital image analysis using Visiopharm software. Results: Metformin treatment was associated with a 41.4% decrease in FOXP3 + T cells in intratumor regions of interest ( P = .004) and a 66.5% increase in stromal CD8 + T cells at the leading edge of the tumor ( P = .021) when compared to pretreatment biopsies. This was reflected in increased CD8 + /FOXP3 + cell ratios within the tumor ( P  < .001) and stromal compartments ( P  < .001). The effects of metformin occurred independently of HPV status. Conclusion: Metformin treatment may favorably alter the immune TME in HNSCC independent of HPV status. Level of Evidence: 1b. This study is most accurately described as a non‐randomized controlled trial and therefore may reflect a level of evidence below 1b but above 2a from the provided "levels of evidence" chart. Laryngoscope, 130:E490–E498, 2020